Chain of blame how Wall Street caused the mortgage and credit crisis - Muolo, Paul. (John Wiley & Sons, 2008)
In the summer of 2007, the subprime empire that Wall Street had built all came crashing down. Banks like Countrywide and non-banks such as New Century Financial--all financed by Bear Stearns, Goldman Sachs, Merrill Lynch, Lehman Brothers and others--were in danger of closing, or actually failing. On average, 50 lenders a month were going bust. Chain of Blame will chronicle the disaster, focusing on the players - the executives on Wall Street but also the lenders and brokers. It's a national story of greed and avaraice, one that hasn't come down the pike since the S&L scandal.--From publisher description.